The Strategy for Developing a Marketplace Promotion Model Based on Artificial Intelligence (AI) to Improve Online Marketing in Indonesia - Sunarta; Budi Permana (Universitas Pendidikan Ganesha, 2024)
The rapid development of Artificial Intelligence (AI) has changed the way human interaction and daily activities are carried out. The limitations of direct human interaction have driven the development of AI, which improves the operational efficiency of organizations. AI has penetrated various industries, especially the digital commerce sector, where AI has become a valuable tool to increase promotion and sales. In the face of these challenges, companies need to wisely integrate AI into their operations to deliver balanced benefits to their customers and businesses. This research focuses on the case study of Tokopedia, a fast-growing online marketplace in Indonesia. The research method used is qualitative with a case study approach, allowing in-depth analysis of complex social phenomena. Internal and external data were collected through in-depth interviews, nonparticipatory observation, and document analysis. The results showed that the AI-based promotion model significantly increased product purchases. This study reveals how Tokopedia successfully leveraged AI technology to increase product appeal, personalize customer experience, and ultimately increase sales. In a competitive digital market, AI-based promotion strategies are crucial to success. The implications of this research show that AI has great potential to transform business operations in the digital marketplace, and companies that are able to optimize AI have a great opportunity to increase sales and achieve success in an increasingly competitive era.